CONCEPTUAL APPROACHES TO HIGH-FREQUENCY TRADING IDENTIFICATION - Ruslan R. Iskyandyarov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the conceptual approaches to the High Frequency Trading identification in order to allocate set of features that enable to separate High Frequency Trading from other forms of exchange activities. At today's exchange trading HFT has a special role, however, it has not yet developed a unified approach to its identification. This is due not only to the complexity of the analysis of big data, but also with a variety of conditions in which operate HFT-robots. Developed a classification features for the purpose of a full characteristics High Frequency Trading from different sides.